2005
DOI: 10.1007/s00018-005-5371-1
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin

Abstract: Mammalian lactoferrin (Lf) receptors are suggested to have pivotal roles for mediating multiple functions of Lf. In this review, we focus on current knowledge of the structure and function of mammalian Lf receptors, mainly the first cloned Lf receptor that has been shown to be expressed in the infant small intestine at high levels but also in virtually all other tissues. The small intestinal Lf receptor takes up iron from Lf into cells and presumably exerts other physiological functions. Other Lf receptors in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
107
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(128 citation statements)
references
References 123 publications
(133 reference statements)
2
107
0
3
Order By: Relevance
“…In the full-length lactoferrin protein, cellular uptake has been described for various cellular systems. Although it has been observed that the polycationic nature of the N terminus by itself confers an interaction with sugars on the cell surface, cellular uptake and the biological effects of lactoferrin have been attributed to its binding to one of the several receptors identified for this protein (48). In contrast to our peptide, binding to these receptors was therefore saturable.…”
Section: Discussionmentioning
confidence: 55%
“…In the full-length lactoferrin protein, cellular uptake has been described for various cellular systems. Although it has been observed that the polycationic nature of the N terminus by itself confers an interaction with sugars on the cell surface, cellular uptake and the biological effects of lactoferrin have been attributed to its binding to one of the several receptors identified for this protein (48). In contrast to our peptide, binding to these receptors was therefore saturable.…”
Section: Discussionmentioning
confidence: 55%
“…В частности, найдены различия в строении рецепторов некоторых органов и тканей человека к обоим лактоферринам. Установлено, что рецепторы тонкой кишки человека более специфич-ны к белку человека, чем к коровьему [57]. Оптимальный показатель рН для связывания нативного лактоферрина со специфическими рецепторами равен 6,5-7,5, что соответствует значению рН тонкой кишки новорожден-ных детей.…”
Section: лактоферрин -иммуногенный белок молокаunclassified
“…Образующиеся при расщеплении лактоферринов лак-тоферрицины у человека и коров различаются как по ами-нокислотному составу, так и по биологической активности [57]. Различия между двумя белками имеются и в особен-ностях гликозилирования, которое, как известно, суще-ственно влияет на активность белка in vivo.…”
Section: лактоферрин -иммуногенный белок молокаunclassified
“…Previous studies on lactoferrin receptors reported that their expression on BBB facilitates the transport of lactoferrin to the brain [80]. Ji and colleagues in 2006 have demonstrated the greater brain uptake of lactotransferrin than that of transferrin and OX26 (an anti-transferrin receptor antibody) through endocytosis mediated by receptors in an in vitro BBB study.…”
Section: Active Targeting By Trojan Horse Approachmentioning
confidence: 99%